System design and application of sewage treatment and the use of recycled water in Dianchi Lake Basin based on WebGIS - Tang Qiaoling; Liang Hong; Guo Yumei; Cun Ruitao (MATEC Web of Conferences, 2017)
In this paper, due to the current problem of sewage treatment in Dianchi Lake Basin in Kunming and the practical demand for the integrated solution of the sewage treatment and reclaimed water use, our team has developed the online management system based on the WebGIS. The online management system is designed based on geographic spatial information mapping technology, WebGIS technology and spatial database technology and finally displayed in the form of thematic map called “Visual information platform for Dianchi Lake Basin sewage treatment and recycling water use”. The system has achieved scientific and informative management for Dianchi Lake Basin sewage treatment and recycling of water use. It also provides comprehensive and accurate basic data and decision support for the improvement of urban water environment and pollution control in Dianchi Lake in Kunming. The online system improves the management efficiency, management level and decision-making capacity of sewage treatment and recycling industries in Kunming, and provide a good demonstration and reference in infrastructure of the city.